2017
DOI: 10.1192/bjp.bp.116.195776
|View full text |Cite
|
Sign up to set email alerts
|

Cancer mortality in patients with schizophrenia: systematic review and meta-analysis

Abstract: Previous studies have reported conflicting results on the association between schizophrenia and cancer mortality.To summarise available evidence and quantify the association between schizophrenia and cancer mortality using meta-analysis.We systematically searched literature in the PubMed and Embase databases. Risk estimates and 95% confidence intervals reported in individual studies were pooled using the DerSimonian-Laird random-effects model.We included 19 studies in the meta-analysis. Among them, 15 studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 53 publications
1
63
1
Order By: Relevance
“…Increased expression of Gal/GalNAc associated enzymes and glycan structures are common in various cancers (Schneider et al, 2017;Xie et al, 2018Xie et al, , 2016Zhou et al, 2013Zhou et al, , 2012 and schizophrenia patients diagnosed with cancer tend to have a longer delay to diagnosis, worse treatment outcomes, and higher mortality rates (Abdullah et al, 2015;Bergamo et al, 2014;Irwin et al, 2017;Ishikawa et al, 2016;Lawrence et al, 2000;Safdieh et al, 2017;Sathianathen et al, 2019;Zhuo et al, 2017). Since we have identified decreased levels of B4GALT1 and GALNT16 in schizophrenia, it is possible that established biomarkers for cancer diagnosis do not have the same degree of predictive accuracy for schizophrenia patients.…”
Section: Discussionmentioning
confidence: 91%
“…Increased expression of Gal/GalNAc associated enzymes and glycan structures are common in various cancers (Schneider et al, 2017;Xie et al, 2018Xie et al, , 2016Zhou et al, 2013Zhou et al, , 2012 and schizophrenia patients diagnosed with cancer tend to have a longer delay to diagnosis, worse treatment outcomes, and higher mortality rates (Abdullah et al, 2015;Bergamo et al, 2014;Irwin et al, 2017;Ishikawa et al, 2016;Lawrence et al, 2000;Safdieh et al, 2017;Sathianathen et al, 2019;Zhuo et al, 2017). Since we have identified decreased levels of B4GALT1 and GALNT16 in schizophrenia, it is possible that established biomarkers for cancer diagnosis do not have the same degree of predictive accuracy for schizophrenia patients.…”
Section: Discussionmentioning
confidence: 91%
“…A specific, related aspect is that this study did not involve patients with severe mental illness (eg, schizophrenia, bipolar disorders, severe personality disorders), for whom the possible use of screening tools for distress should be part of more specific studies. Indeed, the problem of cancer among patients who have severe mental illness and the needs for integrated assessment and intervention deserve to be urgently examined . Third, because of the cross‐sectional nature of the study, conclusions regarding the reliability of the instruments over time, across the illness trajectory, are not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the problem of cancer among patients who have severe mental illness and the needs for integrated assessment and intervention deserve to be urgently examined. 75,76 Third, because of the cross-sectional nature of the study, conclusions regarding the reliability of the instruments over time, across the illness trajectory, are not possible. The importance of prospective evaluation was underlined in a recent, large, prospective German study, 77 which reported a 31.8% prevalence of mental disorders 4 weeks after diagnosis and a 39.8% prevalence at 12 months using the same instrument we used (CIDI).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis published in 2017 revealed that patients with schizophrenia have a slightly decreased risk of overall cancer incidence compared with the general population [25]. Another meta-analysis based on 16 cohort studies showed a high risk of cancer mortality in individuals with schizophrenia [12]. Different from the results of subgroup analysis stratified by cancer type [25], Zhuo et al described that female schizophrenia faced a higher incidence of breast cancer than the general population in a meta-analysis published in 2018 [26].…”
Section: Main Findings and Comparison With Other Studiesmentioning
confidence: 99%